Crime e delinquência: um estudo sobre a caracterização do sujeito criminoso nas Varas de Execuções Penais da Comarca de Vitória, Espírito Santo - Leonardo, Grayce Lourdes Amboss Merçon (2022)
This research aims to study the large area of Crime and Delinquency, which will be discussed in the light of Contemporary Social Theories. The search for such an epistemological bias aims to analyze such social facts outside the punitive hegemonic patterns so common in the modern and contemporary criminal justice system, whose practices have resulted in the criminalization and incarceration of a good part of the black population, the poor, the minority groups and social movements for emancipatory struggles. Understanding these phenomena as part of social relations, which are historically processed, with this study I intend to carry out an investigation that contemplates both the singularity and the scope of the topic of Criminality and Delinquency and, consequently, of the so-called "Criminal/Delinquent Subject ". For that, I make some approximations between Criminal State, Punitive Power and Biopower and between Criminal Subjection and Criminal State. I will use the phenomenon of Criminal Subjection, developed by the sociologist Michel Misse (2010), as a conceptual tool to verify its possible occurrence in criminal proceedings and sentences. In dialogue with the proposed theory, I will use Discourse Analysis (AD) as a methodological resource to analyze criminal proceedings. In AD, discursive production is understood as a social practice, with verbal and written language seen as integral parts of the socio-historical-political-economic context of a certain time and place, thus being producers of meanings and representing practices social. I will make a cut within the large area of Crime and Delinquency and seek to investigate how power acts through criminal legal discourses using punitive devices to exercise control over certain social groups or certain categories of subjects called "bandits", "criminals" , whose phenomenon was called "Criminal Subjection" by the sociologist Michel Misse.